Assessment of Vulnerability Curves of Pircas over Slopes by the Discrete Element Method (DEM) - A Case Study in Carabayllo, Peru - Zanelli C. (2018)
The increase of urban population in seismic areas and the lack of urban planning have caused the occupancy of hazardous zones around most cities in Latin America. Some dwellings in these settlements are located on terraces on steep hills supported by pircas (dry stone retaining walls). Seismic vulnerability analysis of these structures becomes a crucial step to assess the level of damage generated in possible events, and to propose alternatives for risk reduction and prevention. This analysis was conducted through a numerical model based on the discrete element method (DEM), three typologies of pircas where modelled according to a statistical analysis carried out in the case study. Damage state was defined taking into account the maximum displacement response. According to the lateral seismic acceleration in the out of plane direction, four states of damage were defined: slight, moderate, extensive, and complete. Seismic vulnerability curve represents the relationship between the structural damage of pircas and the seismic acceleration. The obtained curve showed that during frequent earthquakes pircas would be in extensive damage, while for occasional earthquakes almost all typologies of pircas would be in complete damage.